(3GdaGNQ aj TQM Led YHOGdbGgQs - (3CHhYHO Gddg TeS GdOjf eMeO Hf CHj GdaJM Hf CHj GdaVd Hj CHj Ydj GdHYdjs; (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEf cJGH GdLed aj GdfMh dYHOGdbGgQ GdLQLGfj bO cKQ GYJfGA GdeHJOFjf aj GdGTJZGd aj GdfMh s
(3BNQgG (B:s
(3hbO JbOe GdcdGe Ydi CcKQ GdVQGFQ aj CHhGHgG CfgGg cJGHI hJCdjakG Je GdcJGH s
(3fbdJ ef CUd fSN ef CUd GdeUfas
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B310s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B124 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B235 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B603s
Keywords: (3GdfMhs